A Hybrid Agent-Based Secondary Control for Microgrids With Increased Fault-Tolerance Needs - Bintoudi, Angelina D.; Zyglakis, Lampros; Apostolos, C. Tsolakis; Ioannidis, Dimosthenis K.; Al-Agtash, Salem Y.; Martinez-Ramos, J. L.; Martensen, Nis; Tzovaras, Dimitrios; Tsolakis, Apostolos C. (Institution of Engineering and Technology, 2018)
This paper proposes a hybrid secondary control architecture for microgrids with AC-coupled droop-controlled units, based on both centralised and distributed control principles. The proposed secondary control is based on a multi-agent system (MAS), complemented by a microgrid centralised controller (MGCC). The system is able to adjust the droop curves dynamically in order to achieve voltage/frequency restoration as well as active/reactive power optimal allocation, based on the actual status of the controllable units, in particular, the state-of-charge of batteries and maximum power point of photovoltaics. The distributed nature of the agents is also fully exploited because the proposed framework retains operability even under fault on secondary MGCC. To evaluate the proposed framework, a scenario-based performance analysis has been tested over a simulated AC islanded microgrid, where communication from the MGCC is suddenly interrupted and the MAS is required to reconfigure in order to maintain the same control objectives. MATLAB/Simulink simulations have been realised using detailed physical form models for a small-scale microgrid, while the implementation of the MGCC and MAS is accomplished through Java Agent Development (JADE) framework. © 2021 Elsevier B.V., All rights reserved.
Keywords: Fault Tolerant Control; Microgrid; Multi-Agent System; Reconfigurable Architectures; Secondary Control; Charging (Batteries); Closed Loop Control Systems; Distributed Parameter Control Systems; Energy Conversion; Fault Tolerance; Matlab; Microgrids; Multi Agent Systems; Control Objectives; Distributed Control; Islanded Microgrid; Matlab/Simulink Simulation; Maximum Power Point; Optimal Allocation; Performance Analysis; Secondary Control; Battery Management Systems